Wavelength tunable InGaN/GaN nano-ring LEDs via nano-sphere lithography - Wang, Sheng-Wen (Sci Rep, 2017)
In this research, nano-ring light-emitting diodes (NRLEDs) with different wall width (120 nm, 80 nm and 40 nm) were fabricated by specialized nano-sphere lithography technology. Through the thinned wall, the effective bandgaps of nano-ring LEDs can be precisely tuned by reducing the strain inside the active region. Photoluminescence (PL) and time-resolved PL measurements indicated the lattice-mismatch induced strain inside the active region was relaxed when the wall width is reduced. Through the simulation, we can understand the strain distribution of active region inside NRLEDs. The simulation results not only revealed the exact distribution of strain but also predicted the trend of wavelength-shifted behavior of NRLEDs. Finally, the NRLEDs devices with four-color emission on the same wafer were demonstrated.